Bis[S-benzyl 3-(furan-2-ylmethylidene)dithiocarbazato-κ2 N 3,S]copper(II): crystal structure and Hirshfeld surface analysis - Enis Nadia Md Yusof,; Nazhirah M Nasri,; Ravoof, Thahira Begum S. A.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
The title CuII complex, [Cu(C13H11N2OS2)2], features a trans-N2S2 donor set as a result of the CuII atom being located on a crystallographic centre of inversion and being coordinated by thiolate-S and imine-N atoms derived from two dithiocarbazate anions. The resulting geometry is distorted square-planar. In the crystal, π(chelate ring)–π(furyl) [inter-centroid separation = 3.6950 (14) A ˚ and angle of inclination = 5.33 (13)˚] and phenyl-C—H...π(phenyl) interactions sustain supramolecular layers lying parallel to (102). The most prominent interactions between layers, as conﬁrmed by an analysis of the calculated Hirshfeld surface, are phenyl-H...H(phenyl) contacts. Indications for Cu...Cg(furyl) contacts (Cu...Cg = 3.74 A ˚ ) were also found. Interaction energy calculations suggest the contacts between molecules are largely dispersive in nature